Eco-Innovation and Employment: A Task-Based Analysis - Robert J. R. Elliott; Wenjing Kuai; David Maddison; Ceren Ozgen (Institute of Labor Economics (IZA), 2021)
This paper provides some of the first evidence of the relationship between eco-innovation and employment. Adopting a O*NET based task approach, in a study of the Dutch firms, we show that eco-innovation has no impact on overall employment. However, compared to non- eco-innovators there is an 18.2% increase in the number of green jobs (equivalent to 12 new green workers for the average firm). This means an average increase in the share of green workers of around 3.3%. Broadly speaking, the increase in the share of green jobs was driven by a reduction in non-green workers and a smaller but still significant increase in the number of green workers. We further show that subsidy-driven policies, rather than regulation-driven policies positively correlate with the number of green workers.
Keywords: Q52; Q55; J23; 330; eco-innovation; green jobs; subsidies